Ovarian suppression impairs sport performance in junior elite female swimmers - VanHeest, J. L.; Rodgers, C. D.; Mahoney, C. E.; de Souza, M. J. (Medicine & Science in Sports & Exercise, 2014)
Introduction: Competitive female athletes restrict energy intake and increase exercise energy expenditure frequently resulting in ovarian suppression. The purpose of this study was to determine the impact of ovarian suppression and energy deficit on swimming performance (400-m swim velocity).